Prolonging the Lifetime of Two-Tiered Wireless Sensor Networks with Mobile Relays. (5th March 2013) - Kotsilieris, Theodore C.; Karetsos, George T.
Abstract : We propose a clustering scheme for wireless sensor nodes in hierarchical wireless sensor networking architectures that employs mobile relay nodes in order to achieve energy conservation and network lifetime prolongation. The key aspects of our scheme are relay node relocation and reclustering when failures are detected. The performance of the proposed approach is evaluated via simulations for various topology layouts based on the sensor node population and number of mobile relay nodes employed. The results show significant energy savings in particular for topologies with large numbers of sensors.